Long Term Survival in Unresectable Stage IV Esophageal Squamous Cell Carcinoma Treated with Chemoradiation - Ameri, Ahmad; Moeini, Bahar; Mofid, Bahram (Reports of Radiotherapy and Oncology, 2013)
Background: Esophageal Squamous Cell Carcinoma is one of the most common GI cancers in Iran. Development of para-aortic lymphadenopathy is classified as stage IV and long term survival is rare. We report a case of esophageal SCC with paraaortic lymphadenopathies, who was treated with systemic and nonsurgical locoregional therapy. Report of the case: A 39-year-old female with SCC of the distal esophagus and proximal stomach, that was unresectable on laparatomy, was referred to our center for palliative treatment. She received six cycles of chemotherapy (Paclitaxel / cisplatin), and then concurrent chemotherapy and radiotherapy to the primary tumor and paraaortic region with a total dose of 5220 centigray (cGy). Six years later, she was still alive without any complaints or disease progression. Conclusion: It seems that patients with locally advanced unresectable Esophageal Squamous Cell Carcinoma can be treated radically with systemic and nonsurgical locoregional therapy, to achieve long term survival